Root growth, yield and stress tolerance of soybean to transient waterlogging under different climatic regimes - Vinay M. Gangana Gowdra; B. S. Lalitha; Hanamant M. Halli; E. Senthamil; Priyanka Negi; H. M. Jayadeva; P. S. Basavaraj; C. B. Harisha; K. M. Boraiah; Sandeep B. Adavi; P. G. Suresha; Raghavendra Nargund; et al. (Scientific Reports, 2025)
Abstract Global warming-induced abiotic stresses, such as waterlogging, significantly threaten crop yields. Increased rainfall intensity in recent years has exacerbated waterlogging severity, especially in lowlands and heavy soils. Its intensity is projected to increase by 14–35% in the future, posing a serious risk to crop production and the achievement of sustainable development goals. Soybean, a major global commercial crop cultivated across diverse climates, is highly sensitive to waterlogging, with yield losses of up to 83% due to impaired root morphology and growth. Therefore, understanding the stage-specific response of soybean to varying intensities of waterlogging under different climate regimes is crucial to mitigate the impact of climate change. This study evaluated two climate regimes (Summer: CS and Rainy: CR), four growth stages (S15: 15 days after emergence, S30, S45, and S60), and five waterlogging durations (D2: 2 days, D4, D6, D8, and D10) using a randomized complete block design (RCBD) with seven replications in 2023. Results revealed that waterlogging adversely affected soybean root morphology (reducing root volume by 8.6% and dry weight by 5.3%) and growth (decreasing leaf area by ~ 6% and dry matter by 48.2%), with more severe effects observed during the summer compared to the rainy season. Among growth stages, soybean was most sensitive at S45, showing greater reductions in growth attributes and seed yield (~ 64.9%) across climate regimes. Prolonged waterlogging (2–10 days) had a pronounced negative impact on root and shoot parameters, resulting in yield reductions of 25.4–47.8% during summer and 47.0–68.2% during the rainy season, compared to the control. Yield stability was highest at D2 (yield stability index: 0.53) with minimal yield reductions, while D10 caused the greatest yield loss (~ 58%). Interestingly, the summer climate regime, characterized by bright sunshine hours and higher temperatures, supported better post-stress recovery, leading to higher grain yields. In conclusion, waterlogging during CR × S45 × D10 caused the most substantial yield reduction (~ 91%).